Preparation and application of proficiency testing sample of carbofuran and dimethomorph in Chili - QIU Xinlei; CHEN Yuhang; FENG Chao; XU Qian; LIN Yuanjie; LE Sunyang; JIN Yu'e; LU Dasheng; WANG Guoquan (Zhongguo shipin weisheng zazhi, 2021)
ObjectiveTo prepare a vegetable matrix reference material with pesticide residues and organize a proficiency testing to assess the performance of domestic laboratories on the quantification of pesticide residues.MethodsThrough simulated field planting, chili sprayed with carbofuran and dimethomorph was used as raw materials to prepare chili matrix reference material with pesticide residues. After preparation, the related evaluation and proficiency testing were carried out. Assigned values were obtained from consensus values by robust analysis and the result were assessed using Z-scores.ResultsThe reference material was assessed to be sufficiently homogeneous and stable (all P >0.05). A total of 155 laboratories, from 30 regions in China participated the proficiency testing, while 142 (91.6%), 5 (3.2%) and 8 (5.2%) laboratories had acceptable performance (|z|≤2.0), warning signal (2.0<|z|<3.0), and unacceptable performance (|z|≥3.0), respectively.ConclusionA chili matrix reference material with pesticide residues was successfully prepared for proficiency testing and the result indicated that most of domestic laboratories had acceptable capability of pesticides quantification in vegetables.